The Effect of Word Formation Strategy on Eighth-grade Students’ Vocabulary Learning - Hidayat, Muizzul; Thamrin, Nur Sehang; Agussatriana, Agussatriana; Arid, Muhammad (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study principally aims to find out whether there is or no effect of Word Formation Strategy on grade eight students’ vocabulary learning. The research samples were taken using purposive sampling, with the total number of samples being 113 students. The research was conducted at SMP Negeri 2 Sirenja. The research methodology adopted was a quasi-experimental research design. To collect the data, the students were given a pre-test and post-test, numbering 30 items. The research data were analyzed using the Mann-Whitney U Test (SPSS 24). The result showed that the test statistic was 0.001, which is less than 0.05, which indicates that the null hypothesis was rejected and the alternative hypothesis was accepted. The findings suggest a significant difference in learning outcomes between the experimental and control groups. This means that the Word Formation Strategy has a significant effect on students’ vocabulary learning.